ANALYSIS OF FRESHWATER LOBSTER GROWTH AND SURVIVAL (Cherax quadricarinatus) FED WITH NATURAL FEED AND CALCIUM CARBONATE SUPPLEMENTATION - Muh. Hasbir; Nursyahran Nursyahran (Jurnal Riset Diwa Bahari (JRDB), 2026)
Feed quality and mineral availability play important roles in determining the growth and survival of freshwater lobster (Cherax quadricarinatus). This study aimed to analyze the effects of natural feed supplemented with calcium carbonate on the growth and survival performance of freshwater lobster. The experiment was conducted from March to April 2025 at the Freshwater Hatchery of Pangkep State Polytechnic of Agriculture using a completely randomized design with three treatments and three replications. The treatments consisted of commercial shrimp pellets (control), Tubifex sp. supplemented with 10% CaCO₃, and earthworms supplemented with 10% CaCO₃. Lobsters were reared for 42 days and fed daily at 3% of biomass. Absolute growth and survival rate were used as response variables, and the data were analyzed using one-way ANOVA followed by Tukey’s HSD test. The results showed that dietary treatments significantly affected both growth and survival (p < 0.05). The highest absolute growth (0.29 ± 0.005 g) and survival rate (88.89 ± 5.55%) were obtained in lobsters fed Tubifex sp. supplemented with 10% CaCO₃, whereas the control treatment produced the lowest values. Water quality parameters remained within acceptable ranges for freshwater lobster culture throughout the study. These findings indicate that the combination of natural feed and calcium carbonate supplementation can enhance growth performance and improve survival in freshwater lobster culture.